Contextual neural dynamics during time perception in the primate ventral premotor cortex - Héctor Díaz; Lucas Bayones; Manuel Alvarez; Bernardo Andrade-Ortega; Sebastián Valero; Antonio Zainos; Ranulfo Romo; Román Rossi-Pool (Proceedings of the National Academy of Sciences, 2025)
Understanding how time perception adapts to cognitive demands remains a significant challenge. In some contexts, the brain encodes time categorically (as “long” or “short”), while in others, it encodes precise time intervals on a continuous scale. Although the ventral premotor cortex (VPC) is known for its role in complex temporal processes, such as speech, its specific involvement in time estimation remains underexplored. In this study, we investigated how the VPC processes temporal information during a time interval comparison task (TICT) and a time interval categorization task (TCT) in primates. We found a notable heterogeneity in neuronal responses associated with time perception across both tasks. While most neurons responded during time interval presentation, a smaller subset retained this information during the working memory periods. Population-level analysis revealed distinct dynamics between tasks: In the TICT, population activity exhibited a linear and parametric relationship with interval duration, whereas in the TCT, neuronal activity diverged into two distinct dynamics corresponding to the interval categories. During delay periods, these categorical or parametric representations remained consistent within each task context. This contextual shift underscores the VPC’s adaptive role in interval estimation and highlights how temporal representations are modulated by cognitive demands.